2018
DOI: 10.1038/s41598-017-18817-6
|View full text |Cite
|
Sign up to set email alerts
|

oriD structure controls RepD initiation during rolling-circle replication

Abstract: Bacterial antibiotic resistance is often carried by circular DNA plasmids that are copied separately from the genomic DNA and can be passed to other bacteria, spreading the resistance. The chloramphenicol-resistance plasmid pC221 from Staphylococcus aureus is duplicated by a process called asymmetric rolling circle replication. It is not fully understood how the replication process is regulated but its initiation requires a plasmid-encoded protein called RepD that nicks one strand of the parent plasmid at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A lookup table for calculating z position was created by stepping the objective using a piezo actuator (P721 PiFoc, Physik Instrumente). Bead positions were tracked, in real time, using a previously described algorithm ( 71 ). The force, F , was calibrated according to the formula F = k b Tl /< x 2 >, where k b is the Boltzmann constant, T is the absolute temperature, l is the DNA extension, and < x 2 > is a variance in bead x position (parallel to the magnetic field lines).…”
Section: Methodsmentioning
confidence: 99%
“…A lookup table for calculating z position was created by stepping the objective using a piezo actuator (P721 PiFoc, Physik Instrumente). Bead positions were tracked, in real time, using a previously described algorithm ( 71 ). The force, F , was calibrated according to the formula F = k b Tl /< x 2 >, where k b is the Boltzmann constant, T is the absolute temperature, l is the DNA extension, and < x 2 > is a variance in bead x position (parallel to the magnetic field lines).…”
Section: Methodsmentioning
confidence: 99%
“…Cruciforms have also been demonstrated to influence various aspects of DNA replication. A range of studies confirmed cruciform formation in the origins of replication in bacteria, yeast, and mammalian cells [ 15 , 103 ]. Furthermore, several proteins involved in replication bind to cruciform structures, such as S16, MLL, WRN, and 14-3-3 ( Table 1 ).…”
Section: A Range Of Proteins Interact With Cruciformsmentioning
confidence: 99%
“…The bead position was tracked by video microscopy using a Nikon TE-2000 microscope, high powered LED illuminator and 60x Nikon air objective. The z-height of the bead was computed by using a look-up table for the diffraction ring pattern [21]. The microscope drift was corrected by subtracting the position of a fiducial silica bead which was bound to the surface.…”
Section: Magnetic Tweezersmentioning
confidence: 99%